2022
DOI: 10.11604/pamj.2022.42.140.35086
|View full text |Cite
|
Sign up to set email alerts
|

Stroke units in Nigeria: a report from a Nationwide organizational cross-sectional survey

Abstract: Introduction stroke is one of the leading causes of death and disability in Nigeria. Stroke unit care is crucial for reducing mortality and morbidity in stroke. This study describes the stroke units' structure, organization, and care process in Nigerian tertiary hospitals. Methods this study is a cross-sectional descriptive organizational survey-based study using an online structured questionnaire to collect information on the stroke units. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Presently, the prevalence of stroke in Nigeria is between 1.14-7.7 per 1000. From 2004- 2021, hospital-based research from various parts of Nigeria revealed a 30-day case fatality rate of about 21.2-40% [ 3 - 6 ] For optimal care and efficient use of the healthcare resources at hand, early evaluation of the severity of the disease, the risk of complications, and the prognosis is crucial [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the prevalence of stroke in Nigeria is between 1.14-7.7 per 1000. From 2004- 2021, hospital-based research from various parts of Nigeria revealed a 30-day case fatality rate of about 21.2-40% [ 3 - 6 ] For optimal care and efficient use of the healthcare resources at hand, early evaluation of the severity of the disease, the risk of complications, and the prognosis is crucial [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 2018 meta-analysis of eleven selected studies covering 1995 -2016 reported prevalence of 27.4 per 100,000 from 2010 upwards (Adeloye et al, 2019). In the sub-Saharan Africa, stroke has a very poor outcome and the 30-day case fatality range in Nigeria was quoted to be 21.2 -40.0% (Arabambi et al, 2022). Ischemic stroke is reversible with timely diagnosis and appropriate intervention.…”
Section: Introductionmentioning
confidence: 99%